INOVASI PEMBELAJARAN INSTALASI MOTOR LISTRIK BERBASIS SIMULASI DIGITAL: IMPLEMENTASI SIMURELAY PADA MATERI RANGKAIAN DOL - Risna, Mega; Maksum, Hasan; Novaliendry, Dony (ACADEMIA: Jurnal Inovasi Riset Akademik, 2025)
This study is motivated by the limited availability of practical facilities in motor installation learning at vocational high schools, which reduces students’ practice frequency and leads to suboptimal mastery of concepts and psychomotor skills, particularly in the Direct Online (DOL) motor starter topic. The focus of this research is to analyze the effectiveness of the SimuRelay digital simulation application as a learning medium for improving students’ learning outcomes on DOL material. The study employed a quantitative approach with a one-group pretest–posttest design involving 32 students of class XI TITL 2 at SMK Negeri 8 Palembang. The research procedures included instrument preparation, implementation of simulation-based learning, administration of pretest and posttest, and psychomotor assessment using an observation rubric. Data were analyzed by comparing pretest and posttest scores and conducting descriptive analysis for the psychomotor domain. The results showed an increase in the average score from 61.6 on the pretest to 80.2 on the posttest, with all students (100%) demonstrating improvement. The highest score increased from 75 to 90, while the lowest rose from 50 to 60, indicating that SimuRelay-based learning had a uniformly positive impact on all students. Psychomotor observations revealed improvement in students’ understanding of contactor working logic, self-holding circuits, and troubleshooting steps. It is concluded that the SimuRelay digital simulation effectively enhances cognitive learning outcomes and supports the development of basic practical skills, making it a relevant alternative learning medium for schools with limited laboratory facilities. ABSTRAK Penelitian ini dilatarbelakangi oleh keterbatasan sarana praktik pada pembelajaran instalasi motor listrik di SMK yang menyebabkan rendahnya frekuensi latihan siswa dan berdampak pada kurang optimalnya penguasaan konsep serta keterampilan psikomotorik, khususnya pada materi rangkaian Direct Online (DOL). Fokus penelitian ini adalah menganalisis efektivitas penggunaan aplikasi simulasi digital SimuRelay sebagai media pembelajaran untuk meningkatkan hasil belajar siswa pada materi DOL. Penelitian menggunakan pendekatan kuantitatif dengan desain one-group pretest-posttest yang melibatkan 32 siswa kelas XI TITL 2 SMK Negeri 8 Palembang. Langkah penelitian meliputi tahap persiapan instrumen, pelaksanaan pembelajaran berbasis simulasi, pemberian pretest dan posttest, serta penilaian psikomotorik melalui rubrik observasi. Data dianalisis menggunakan perbandingan nilai pretest-posttest serta analisis deskriptif untuk ranah psikomotorik. Hasil penelitian menunjukkan peningkatan nilai rata-rata dari 61,6 pada pretest menjadi 80,2 pada posttest, dengan seluruh siswa (100%) mengalami peningkatan skor. Nilai tertinggi meningkat dari 75 menjadi 90, sedangkan nilai terendah dari 50 menjadi 60, menunjukkan bahwa pembelajaran melalui SimuRelay memberi dampak merata pada seluruh siswa. Secara psikomotorik, siswa menunjukkan peningkatan kemampuan dalam memahami logika kerja kontaktor, alur self holding, dan identifikasi gangguan rangkaian. Disimpulan bahwa simulasi digital Simurelay efektif meningkatkan hasil belajar kognitif dan mendukung penguatan keterampilan dasar praktik, sehingga dapat menjadi alternatif media pembelajaran yang relevan pada kondisi sekolah dengan keterbatasan fasilitas.